Four elders journeying ageing in isolation during uncertain or anxious times: an elder-directed, cross-disciplinary project about faith. Issue 1 (2nd January 2023) - Short, Monica; Burningham, Giselle; Wright, Jenny; Wardle, Sabine; Byford, Ed; Osburn, Lynelle
ABSTRACT: The role of spirituality and faith remains crucial for positive ageing. However, the voices and experiences of elders during and post-pandemic are understated. This elder-directed autoethnography considers the question: What role did your faith play in coping with social isolation? Four Christian elders narrate their spiritual journey leading to hope in uncertain times. The narratives highlight how their faith, routine, and rituals are bringing them calm, building resilience, and helping them cope with the dynamism of living in isolation. While the pandemic is immensely challenging, it is also providing the opportunity for reflection, faith-building, and encouragement to surrender to God.